2012
DOI: 10.1161/jaha.112.002956
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 4, A Novel Circulating Biomarker for Oxidative Stress and the Risk of Incident Cardiovascular Disease and All‐Cause Mortality

Abstract: BackgroundOxidative stress has been suggested to play a key role in the development of cardiovascular disease (CVD). The aim of our study was to investigate the associations of serum peroxiredoxin 4 (Prx4), a hydrogen peroxide–degrading peroxidase, with incident CVD and all-cause mortality. We subsequently examined the incremental value of Prx4 for the risk prediction of CVD compared with the Framingham risk score (FRS).Methods and ResultsWe performed Cox regression analyses in 8141 participants without histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 56 publications
(135 reference statements)
4
29
0
Order By: Relevance
“…60 Prx4 has been proposed to be a biomarker of oxidative stress based on evidence that patients with increased Prx4 have elevated CVD risk and mortality. 61 Prx6 exhibits both glutathione peroxidase and phospholipase A 2 activities, and is necessary for activation of Nox2 in endothelial cells and neutrophils. 62 …”
Section: Antioxidantsmentioning
confidence: 99%
“…60 Prx4 has been proposed to be a biomarker of oxidative stress based on evidence that patients with increased Prx4 have elevated CVD risk and mortality. 61 Prx6 exhibits both glutathione peroxidase and phospholipase A 2 activities, and is necessary for activation of Nox2 in endothelial cells and neutrophils. 62 …”
Section: Antioxidantsmentioning
confidence: 99%
“…[14][15][16] Some studies demonstrate that the increased levels of peroxiredoxin are linked to higher risk of cardiovascular diseases and increased cardiovascular mortality. 17 In patients with diabetes, peroxiredoxin levels are also correlated with cardiovascular complications and in combination with traditional risk factors have a predictive value for cardiovascular mortality risk. 18 There are, however, no data about its role in prediabetic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Also, PRDX4 is secreted into an extracellular environment, therefore, its plasma concentration may be used as a molecular indicator of various cardiovascular disease and other disorders involving oxidative stress (Schulte, 2011). The increased serum PRDX4 concentration is considered as a good indicator of risk to cardiovascular disease because cardiovascular disease have higher level of oxidative stress and PRDX4 is overexpressed in these conditions (Abbasi et al, 2012). A study in a rat model of Wilson's disease has demonstrated that this disease has a lower level of PRDX4 expression as compared to normal (Ito et al, 2012).…”
Section: Tumor Promoting Effect Of Prdx4mentioning
confidence: 99%